ChemInform Abstract: Large Scale Synthesis and Formation Mechanism of Highly Magnetic and Stable Iron Nitride (ε‐Fe3N) Nanoparticles. Issue 38 (3rd September 2015) - K., Rohith Vinod; Saravanan, P.; Sakar, M.; Vinod, V. T. P.; Cernik, Miroslav; Balakumar, S.
Abstract ε‐Fe3N magnetic nanospheres of an average 45 nm size are prepared by nitriding Fe nanoparticles with gaseous NH3 (alumina boat, 650 °C, 4 h).